PENDAMPINGAN MASYARAKAT DUSUN TLOCOR DALAM PENGOPTIMALAN SANITASI DAN EKSISTENSI PARIWISATA DI KABUPATEN SIDOARJO - Juli Nurani; Priyono Priyono (Yayasan Pendidikan dan Kebudayaan Dharma Wacana, 2020)
Sanitation is an effort to foster and create a good condition in the field of health, especially public health. Basically, sanitation has a goal to be able to guarantee the cleanliness of the human environment so that a condition that is in accordance with the health community is realized. Tlocor Hamlet is a coastal hamlet located on the coast of Sidoarjo Regency and is still included in the area of Kedung Pandan Village, Jabon District. As one of the Dusun with a tourist destination, Tlocor Maritime Tourism which is also an access to go to the island resulting from the Sidoarjo mud disaster, better known as Lusi Island, it is better for the people of Tlocor Hamlet to maintain cleanliness and sanitation in the area they live in especially in the area they live in. they are one tourist destination. Based on field surveys that have been conducted previously and interviews with several informants such as village officials to the local RT head about problems that are happening and need more attention that we hope to improve and improve, as well as the results of discussions with the Tlocor Maritime Tourism manager namely the Tourism Awareness Group (Pokdarwis), our work program we divide into two outlines in the field of sanitation optimization which includes sanitation education, introduction of waste disposal schemes, to training in making souvenirs based on used materials, as well as the Tourism Existence optimization program which includes a photo spot making program, introduction public through information media and training in making tofu shrimp as a form of utilization of Tlocor's main commodity.